Performance analysis of spring wheat genotypes under rain-fed conditions in warm humid environment of Nepal - Puri, Ramesh Raj; Gautam, Nutan Raj (International Journal of Environment, 2015)
Around 25% of total wheat area in Terai of Nepal falls under rain-fed and partially irrigated condition. A Coordinated varietal trial (CVT) was conducted during two consecutive crop cycles (2011-12 and 2012-13) under timely sown rain-fed conditions of Terai. The trial was conducted in Alpha Lattice design with two replications at Nepal Agricultural Research Council, National Wheat Research Program, Bhairahawa and Nepal Agricultural Research Council, Regional Agriculture Research Station, Nepalgunj. Observations were recorded for yield and yield traits and analyzed using statistical software Cropstat 7.2.The combined analysis of coordinated varietal trial showed that BL 3978 possessed the highest yield (2469.2 Kg ha-1) followed by NL 1097 (2373.2 Kg ha-1) and NL 1094 (2334.06 Kg ha-1). Genotype x Environment interaction for grain yield was significant (p